Regional-Based Tourism Analysis: The Case Of Cavite Province, Philippines - Tadeo, Jerico Bajen; Dela Rea Mendoza, Xavier Lawrence (Institut Pariwisata dan Bisnis Internasional, 2024)
Tourism is indispensable in promoting a country's culture and heritage by educating visitors about local customs, beliefs, and perspectives. Global tourism has increased, and there has been increased interest in studying its impacts from the perspective of host communities. Hence, this study attempted to study the tourism traffic volume and its behavioral influence on the province's income through descriptive-causal design. It showed that the lowest number of tourists in the province of Cavite, with 63,940, was recorded in 2012 in the pre-pandemic period and 2020 during the pandemic, whilst the local government's income peaked in 2017 and 2021. Considerably, there was an established influence of tourism traffic volume on the income of the local government unit. The researchers concluded that tourism positively influenced the income of local government units and recommended a localized marketing strategy to further maximize the benefits of tourism in the province.